2015
DOI: 10.1117/1.jpe.5.057610
|View full text |Cite
|
Sign up to set email alerts
|

Alternative model for injection-limited current into organic solids

Abstract: This study demonstrates an analytical relation that models the carrier injection in metal-organic interfaces and which considers two consecutive carriers hopping as the injection mechanism. The new formula has superior attributes and can surpass conventional relations, in particular the thermionic emission-diffusion formula. For example, the model can properly trace the temperature dependency of the injection up to temperatures as low as 30 K and the full range of electric fields. Also, the prominence of joule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The current density–voltage ( J–V ) characteristics of the fabricated UV detectors were measured under dark and UV light and are shown in Figure (a). It can be clearly observed that the devices exhibit typical rectifying behavior in dark, indicating the formation of a simple p‐n junction at the interface of ZnO NPs and BFE polymer . While the device exhibits rectification ratio of 64 at ±1.5 V, its dark current density is 1.3 × 10 −7 A/cm 2 at −1.5 V. This value is the range of the lowest reported values for UV photodetectors with TiO 2 /PVK and ZnO/PFH structures.…”
Section: Resultsmentioning
confidence: 77%
“…The current density–voltage ( J–V ) characteristics of the fabricated UV detectors were measured under dark and UV light and are shown in Figure (a). It can be clearly observed that the devices exhibit typical rectifying behavior in dark, indicating the formation of a simple p‐n junction at the interface of ZnO NPs and BFE polymer . While the device exhibits rectification ratio of 64 at ±1.5 V, its dark current density is 1.3 × 10 −7 A/cm 2 at −1.5 V. This value is the range of the lowest reported values for UV photodetectors with TiO 2 /PVK and ZnO/PFH structures.…”
Section: Resultsmentioning
confidence: 77%
“…The numerical model solves four equations self-consistently to obtain the dynamic of the carriers 47 61 62 . The carrier transition between the electrode and the organic molecules was formulated by Bardeen tunneling theory and basically accounts for the localized nature of the electronics states in the organic solids 61 63 64 :…”
Section: Methodsmentioning
confidence: 99%
“…The carrier transition among the organic molecules with localized states was modeled by the master equation as follows 47 61 62 64 :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the application of metal buffers such as indium has been presented to enhance device properties . Also, many studies have been conducted in order to understand the physics of carrier transfer at the metal/organic interface in an OLED structure.…”
Section: Introductionmentioning
confidence: 99%